Three dimensional reconstruction of late post traumatic orbital wall defects by customized implants using CAD-CAM, 3D stereolithographic models: A case report - Vignesh U.; Divya Mehrotra; Dichen; Vaibhav Anand; Debraj Howlader (Elsevier, 2017)
Aim: Purpose of this case report is to highlight the precision and accuracy obtained with patient specific implants for orbital reconstruction designed on the basis of volumetric analysis of orbital computed tomographic scan (CT) scans using virtual planning, computerised designing and manufacturing and stereolithographic models to correct late post-traumatic orbital deformities such as enophthalmos and diplopia. Material and methods: This case report describes a patient who visited our outpatient clinic for correction of enophthalmos and persistent diplopia in upward gaze, seven months post trauma. Three dimensional (3D) virtual treatment planning was carried out by using the 3D CT data. The unaffected orbit of the contralateral side was superimposed on the deformed orbit to highlight the defect and a customized implant was designed in the desired size and shape on the virtual model using computer aided designing and manufacturing (CAD-CAM) and milled in titanium mesh for precise anatomic orbital reconstruction. Results: There was a marked improvement in both the diplopia in upward gaze and enophthalmos post surgery when the customized patient specific orbital implant was used. Conclusion: The concept of using customized implant with the help of 3D virtual treatment planning, 3D stereolithographic models and CAD-CAM greatly improves the correction of extremely difficult late post-traumatic orbital deformities.